Quadric hologram-based self-conjugation of vortex beams - Polyanskii, P.V.; Felde, Ch.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2005)
Self-conjugation of singular (vortex) beams by a static nonlinearly recorded hologram is reported. Diagnostics of phase-conjugated vortices is implemented using an original technique based on Young’s model of diffraction phenomena. It has been shown that the phase-conjugated vortex is characterized by the same topological charge as the vortex reversed through four-wave degenerate mixing being different in sign from the vortex reflected by a common mirror.